Efectos de la excusa legítima para no autorizar actos en el ejercicio notarial - Ruiz Erazo, Gladys Margarita (2026)
The research addresses the effects of the legitimate excuse for not authorizing acts in the notarial practice, starting from a central problem: the regulatory ambiguity of the Notarial Law, which allows notaries to refrain from authorizing acts or contracts for “legitimate reason or excuse”, without clearly defining what this figure consists of. This lack of definition generates legal uncertainty, as it leaves the decision to excuse oneself to the discretion of the notary, opening space for arbitrary or inconsistent decisions. The objective of the research was to determine how this figure affects legal certainty, based on a normative, doctrinal and jurisprudential analysis. Methodologically, a qualitative, descriptive and non-experimental design approach was applied, based on documentary analysis and legal interpretation of norms such as the Notarial Law, the General Organic Code of Proceedings and the Constitution of the Republic. The results show that, although the Notarial Law establishes certain specific prohibitions for notaries, such as not intervening in acts in which they have direct interest or in which close relatives participate, these grounds have not been systematized as legitimate excuses within a clear and uniform framework. Among the most relevant findings, a direct relationship was identified between the notarial excuse and constitutional principles such as impartiality, legality and independence. It is concluded that the legitimate excuse is an essential tool to preserve public faith and legal certainty, but its effectiveness depends on a future legal reform that develops and clearly typifies its causes and procedure.